Coagulation in Inflammatory Diseases of the Central Nervous System - Chapman, Joab (Seminars in Thrombosis and Hemostasis, 2013)
Thrombin and other proteases involved in coagulation also have the potential to stimulate inflammation in the brain to a large extent through the protease-activated receptors (PARs). Such exposure of the brain to increased levels of coagulation factors is more likely to occur during vasculitis and activation of intrinsic coagulation in the brain and may cause inflammatory diseases such as multiple sclerosis. There is growing evidence from animal models and human brain samples that links upregulation of coagulation factors to inflammatory central nervous system (CNS) disease. Evidence includes measures of thrombin-like activity, levels of its receptors, PARs, and inhibitors of the coagulation pathway. The major receptor for thrombin, PAR-1, has now been definitively located to the synapse and node of Ranvier and its excessive activation leads to blocks in long-term potentiation and in nerve conduction. There is growing evidence that modulating coagulation in models of CNS inflammatory disease has beneficial clinical effects. These findings suggest that coagulation-like pathways play a significant role in the pathogenesis of inflammatory diseases in the CNS and present a viable target for therapeutic strategies.
Keywords: multiple sclerosis; antiphospholipid syndrome; thrombin; synaptic function; conduction block